2015
DOI: 10.3109/11038128.2015.1044561
|View full text |Cite
|
Sign up to set email alerts
|

Client-centred ADL intervention after stroke: Significant others’ experiences

Abstract: Enablement is important also for the significant others of people with stroke. One way of enabling significant others to maintain an active lifestyle and find respite in everyday life might be to enable people with stroke to formulate and act upon their desired activity goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
1
12
0
2
Order By: Relevance
“…The four studies in this thesis evaluate a complex intervention through different perspectives and methods. The various studies, taken together with other studies in this research project (31,71,88,108,109) , provide new knowledge in the context of a client-centred ADL intervention. In this thesis, two of the studies (Study I and II) were designed to compare the effects of the CADL to those of the UADL in the primary outcome "participation" (SIS domain eight) and secondary outcomes during one year.…”
Section: Evaluating Complex Interventionsmentioning
confidence: 98%
See 2 more Smart Citations
“…The four studies in this thesis evaluate a complex intervention through different perspectives and methods. The various studies, taken together with other studies in this research project (31,71,88,108,109) , provide new knowledge in the context of a client-centred ADL intervention. In this thesis, two of the studies (Study I and II) were designed to compare the effects of the CADL to those of the UADL in the primary outcome "participation" (SIS domain eight) and secondary outcomes during one year.…”
Section: Evaluating Complex Interventionsmentioning
confidence: 98%
“…In a recently published study of dyads in stroke (70), the caregivers reported taking greater responsibility for household chores and needing to take more initiatives and responsibility for safety, planning and creating routines for everyday life. However, another study (71) showed that when people with stroke acted as agents in their daily activities, it also influenced the significant others in their interaction and seemed to support the significant others who "took responsibility and achieved a balance with respect to self-esteem in order to get on with everyday life".…”
Section: Significant Othersinformal Care and Caregiver Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke can lead to a stressful situation for family members, with restricted participation, reduced life satisfaction and perceived burden among caregivers [ 6 , 7 ]. A general aim for most rehabilitation programmes for people with stroke is, therefore, to involve the persons’ family in order to attain maximum participation in activities in daily living (ADL) [ 8 ]. Contemporary theories have been confirmed in empirical studies in rehabilitation after stroke, and have shown strong evidence of positive effects of ADL interventions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the situation of informal caregivers vis-à-vis patients who have had a stroke has shown increased and additional responsibilities for caregivers, leading to decreased time for leisure and paid work [30]. Being an informal caregiver thus may affect the caregiver’s own health [31, 32]. …”
Section: Discussionmentioning
confidence: 99%